Kinematic analysis of the relationship between Modic changes and sagittal balance parameters in the cervical spine - Ma, Zikun (Medicine (Baltimore), 2017)
The aim of this study is to investigate the relationship between the Modic changes (MCs) and sagittal parameters of the cervical spine. We conducted a retrospective review of 100 outpatients with magnetic resonance imaging (MRI) scans of the cervical spine (50 male and 50 female). MRI parameters were measured, including neck tilt, T1 slope (T1 ), thoracic inlet angle (TIA), and cervical lordosis (CL: Cobb C2–7). Patients were divided into 4 groups according to the presence or absence of MC and T1s, respectively: MC(+) and MC(−) groups, as well as H-T1s (T1s ≥25°) and L-T1s subgroups (T1s <25°). Relationships between the MC and sagittal alignment in the cervical spine and other parameters were evaluated via Spearman correlation coefficient. Radiologic parameters were compared between the MC(+) group and MC(−) group, and the prevalences of MC were compared between the H-T1s and L-T1s groups. T1s was significantly correlated with TIA and CL, with correlation coefficients of 0.562 and 0.725, respectively. T1 slope was significantly higher in patients with MC than those without MC (P = .041), and the prevalence of MC was higher in the H-T1s group than the L-T1s group (37.5% and 17.1%, respectively). However, the relationship between the parameters of sagittal balance and MC was not significant. The present study demonstrated that high T1 slope is a potential risk factor for the development of MC due to impaired sagittal balance, especially in the C5–6 cervical segment.